Application of FOCUS-PDCA cycle in enhancing the standardization of emergency collaboration among thoracic surgery nurses - Anlong Wang; Yiting Luo; Hui Xu; Ting Fang (Scientific Reports)
Abstract To explore the effectiveness of the FOCUS-PDCA (Find, Organize, Clarify, Understand, Select, Plan, Do, Check, Act) management cycle in improving the standardization of emergency collaboration among thoracic surgery nurses. Forty nurses from two thoracic surgery wards at Zhejiang Cancer Hospital were selected as study subjects. The FOCUS-PDCA cycle was implemented to conduct mixed-mode emergency training, and the standardization scores of nursing operations, job competency self-assessment, and emergency collaboration before and after implementation were compared. After the implementation of FOCUS-PDCA, the assessment scores of nursing operations such as defibrillation, cardiopulmonary resuscitation, suction, tracheal intubation cooperation, and the use of nasal high-flow humidification therapy devices, as well as self-assessment scores of job competency and emergency collaboration standardization, were higher than those before the implementation (p < 0.05). The implementation of FOCUS-PDCA helps improve the standardization of emergency collaboration among thoracic surgery nurses. It should be appropriately carried out according to the department’s situation to promote continuous improvement in nursing quality and emergency response levels.